Effect of six weeks ubiquinol supplementation on mitochondrial respiratory function and exercise capacity in healthy males - Jarred P. Acton; Nehal S. Alsharif; Jack W. Bond; Stuart P. Cocksedge; Abbie G. Mclellan; Donald L. Peden; Mark P. Funnell; Hannah F. Dugdale; Lewis J. James; Richard A. Ferguson; Tom Clifford; Stephen J. Bailey (European Journal of Applied Physiology, 2026)
Coenzyme Q10 (CoQ 10 ) is an integral component of the mitochondrial electron transfer system. Most studies have administered the oxidised form of CoQ 10 (ubiquinone) and observed no effects on mitochondrial respiratory function or endurance exercise performance. The reduced form of CoQ 10 , ubiquinol (UQH 2 ), has greater bioavailability than ubiquinone, but the effects of UQH 2 supplementation on mitochondrial respiratory function and exercise capacity are unclear. Fifty-four healthy, recreationally active males were randomised to receive either 300 mg·day − 1 UQH 2 or placebo (PLA) for 6 weeks in a double-blind independent-group design. Before and after the supplementation period, skeletal muscle mitochondrial respiration variables and protein content of the mitochondrial leak proteins, adenine nucleotide translocase1 + 2 (ANT1 + 2) and uncoupling protein-3 (UCP-3), were assessed. In addition, participants completed a severe-intensity cycle test to exhaustion to assess time to the limit of tolerance (T Lim ) and oxygen uptake (V̇O 2 ) kinetics. Compared to pre-supplementation and PLA, UQH 2 supplementation increased plasma [CoQ 10 ] ( P < 0.05), and lowered inverse respiratory control ratio (Pre-PLA: 0.064 ± 0.034 vs. Post-PLA: 0.072 ± 0.026; Pre- UQH 2 : 0.073 ± 0.039 vs. Post-UQH 2 : 0.044 ± 0.019; P < 0.05), suggestive of improved oxidative phosphorylation coupling efficiency. There were no differences in ANT1 + 2 or UCP-3 protein content post-supplementation compared to pre-supplementation between groups ( P > 0.05). End-exercise V̇O 2 , change in V̇O 2 between 2 min and end-exercise, and T Lim were not different between groups post-supplementation ( P > 0.05). Six-weeks UQH 2 supplementation increased plasma [CoQ 10 ] and oxidative phosphorylation coupling efficiency, but did not alter mitochondrial leak proteins, T Lim or V̇O 2 kinetics during severe-intensity exercise in healthy, active males.

Relationship between attentional bias and stimulus control: An observational study of real-world eating patterns - Stefania Franja; Katherine G. Elliston; Anna E. McCrae; Allison J. Matthews; Stuart G. Ferguson (Appetite, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Ecological momentary assessment of temptations and lapses in non-daily smokers - Saul Shiffman; Sarah M. Scholl; Jason Mao; Stuart G. Ferguson; Donald Hedeker; Hilary A. Tindle (Psychopharmacology, 2020)

The effect of varenicline and nicotine patch on smoking rate and satisfaction with smoking: an examination of the mechanism of action of two pre-quit pharmacotherapies - Wenying Lu; Kate Chappell; Julia A. E. Walters; Glenn A. Jacobson; Rahul Patel; Natalie Schüz; Stuart G. Ferguson (Psychopharmacology, 2017)

An exploratory examination of the mechanisms through which pre-quit patch use aids smoking cessation - Natalie Schüz; Stuart G. Ferguson (Psychopharmacology, 2014)

Effect of high-dose nicotine patch on craving and negative affect leading up to lapse episodes - Stuart G. Ferguson; Saul Shiffman (Psychopharmacology, 2014)

Cue reactivity in non-daily smokers - Saul Shiffman; Michael S. Dunbar; Thomas R. Kirchner; Xiaoxue Li; Hilary A. Tindle; Stewart J. Anderson; Sarah M. Scholl; Stuart G. Ferguson (Psychopharmacology, 2013)

Immediate hedonic response to smoking lapses: relationship to smoking relapse, and effects of nicotine replacement therapy - Saul Shiffman; Stuart G. Ferguson; Chad J. Gwaltney (Psychopharmacology, 2006)

Reduction of abstinence-induced withdrawal and craving using high-dose nicotine replacement therapy - Saul Shiffman; Stuart G. Ferguson; Chad J. Gwaltney; Mark H. Balabanis; William G. Shadel (Psychopharmacology, 2006)

Rhodobacter capsulatus strain BK5 possesses a membrane bound respiratory nitrate reductase rather than the periplasmic enzyme found in other strains - Anna L. Ballard; Alastair G. McEwan; David J. Richardson; J. Baz Jackson; Stuart J. Ferguson (Archives of Microbiology, 1990)

The role of auxiliary oxidants in maintaining redox balance during phototrophic growth of Rhodobacter capsulatuspropionate or butyrate - David J. Richardson; Glenn F. King; David J. Kelly; Alastair G. McEwan; Stuart J. Ferguson; J. Barry Jackson (Archives of Microbiology, 1988)

The role of auxiliary oxidants in maintaining redox balance during phototrophic growth of Rhodobacter capsulatus on propionate or butyrate - David J. Richardson; Glenn F. King; David J. Kelly; Alastair G. McEwan; Stuart J. Ferguson; J. Barry Jackson (Archives of Microbiology, 1988)

The activities of two pathways of nitrate reduction in Rhodopseudomonas capsulata - Kassem Alef; J. Barry Jackson; Alastair G. McEwan; Stuart J. Ferguson (Archives of Microbiology, 1985)

Rationalization of properties of nitrate reductases in Rhodopseudomonas capsulata - Alastair G. McEwan; J. Barry Jackson; Stuart J. Ferguson (Archives of Microbiology, 1984)

Electron flow to dimethylsulphoxide or trimethylamine-N-oxide generates a membrane potential in Rhodopseudomonas capsulata - Alastair G. McEwan; Stuart J. Ferguson; J. Barry Jackson (Archives of Microbiology, 1983)